ANALISIS PERMOHONAN CONSERVATOIR BESLAG BENDA BERGERAK MILIK PERUSAHAAN DITINJAU DARI PRINSIP RIJDENDE BESLAG (STUDI KASUS PUTUSAN NO.42/PDT.G/2017/PN.TNG) - Ignatius Putra Jaya Simanullang; Stanislaus Atalim (Fakultas Hukum Universitas Tarumanagara, 2021)
Confiscate guarantee means that in order to guarantee the implementation of a decision at a later date, the property of the defendant, both movable and immovable during the litigation process, is confiscated first, or in other words that the confiscated goods cannot be confiscated. transferred, traded or transferred to another person. Based on article 227 paragraph (1) HIR, confiscation of collateral can only be applied in cases of debts, but in practice, its application is expanded to include disputes over claims for compensation either arising from Act Against the Law based on 1365 of the Civil Code, in the form of material compensation and compensation. immaterial. The confiscation of collateral has one of the principles, namely the principle of rijdende beslag which in that principle is the confiscation of collateral which is placed on the property of the defendant at the request of the plaintiff. The confiscated Rijdende Beslag were company assets. The custody and management of the company may not be left to the plaintiff, so the business activities of the defendant are not prohibited. Like the case that was tried in the Tangerang District Court with Decision Number 42/Pdt.G/2017/PN.TNG regarding the Compensation Claim which is an unlawful act. The judge considered the confiscation of collateral for losses in the case between PT Hokari Linex Pratama and PT Arimbi Jaya Agung Group. Regarding the reasons for the refusal to confiscate the collateral, which has been decided by the Tangerang District Court, it is contrary to the principle of rijdende beslag which states that the defendant's property can be used as an object of Confiscate guarantee without reducing the business activities of the defendant.